Provide good service quality to satisfy students needs and make them become loyal students - Liew, kok keong; Baharun, Rohaizat; Abdul Wahid, Nabsiah (International Journal of Supply Chain Management, 2018)
This research studies the relationship between student satisfaction and student loyalty within the higher education service. More specifically, it examines the cognitive and affective aspects of students’ satisfaction, to see whether the satisfaction will lead to loyalty. From the 329 responses obtained from students in the public university in Malaysia, the study finds that the relationship between student satisfaction and student loyalty was only partially supported. For cognitive dimensions, “feedback and assessment” and “perceived benefits” of each course showed positive and significant relations to “positive word of mouth”. But, “feedback and assessment” showed negative relations to “complaining behaviour”. “Physical environment”, and “feedback and assessment” were found significant and having positive relations to the “willingness to pay more”. “Physical environment” showed negative relation to “switching behaviour”. For the affective dimensions, “negative emotions” showed negative significant relations to “positive word of mouth”. The study has shown the relationship among the variables that contribute to satisfaction and loyalty. Higher educational institutions could consider these factors as indicators or pointers which would offer as an added advantage to providing standards of service quality to satisfy students’ needs and make them become loyal students.